Removal of methylene blue from aqueous solution by green Synthesized silicon dioxide Nanoparticles using Sunflower Husk - Inas S. Aldabagh; Doha Neithal Saad; Eman I. Ahmed (Chemical Engineering Journal Advances, 2024)
Methylene blue (MB) is a well-known dye that is used in many industries and is highly polluting to the environment. Therefore, this paper proposes using sunflower husks (SFH) through a coating with a nanomaterial made of silicon dioxide (SiO2) with a weight percentage (w/w) of 5:1 to produce (SFH-SiO2) nanoparticles for removing MB from aqueous solutions. This method, known as green synthesis, is characterized by being environmentally friendly and low-cost, as well as efficient in the removal process. The prepared composite was characterized by conducting analysis using Field emission scanning electron microscopy (SEM) with (EDX), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR) were used to look at the samples. The optimal conditions for the removal process were found to be at a pH of 6, with 0.2 g/50 mL of dose adsorbent. At a temperature of 25 °C, the best time to remove the dye was 150 min. With a maximal adsorption capacity (qmax) of 70.16 mg g−1, the findings match the Freundlich model. The adsorption process follows a pseudo-second-order. The negative value of Gibbs free energy (ΔG°) indicated the reaction was spontaneous. (SFH-SiO2) nanoparticles could represent a suitable method for removing cationic dyes from aquatic environments.